What wood is that? : a manual of wood identification with 40 actual wood samples and 79 illustrations - Edlin, Herbert L. (The Viking Press, 1969)
This handy manual contains forty actual samples of woods in popular use, accurately shows each wood's natural color, grain and texture, classifies woods by an ingenious system of fourteen key characteristics, facilitates quick, easy identification of woods, wherever you may find them, ensures prompt, precise identification of trees by their leaves, fruits and bark, tells how and where each wood is grown and describes its special features, explains techniques of lamination, veneering, directional sawing, planing, turning, carving, preserving, moulding, bending, seasoning, preserving and finishing, offers invaluable information for every homeowner, hobbyist, carpenter, dealer, builder, architect and craftsman and provides an important educational tool for teachers, guides and nature lovers.